IMPLEMENTASI GREEN SUPPLY CHAIN PADA INDUSTRI MANUFAKTUR UNTUK MENGURANGI PRODUK DEFECT PRODUKSI PLYWOOD PADA PT. SXX - Azizah, Sinta Nur; Indrasari, Lolyka Dewi (JURNAL REKAYASA SISTEM INDUSTRI, 2025)
This study aims to analyze the types and root causes of plywood product defects in the production process at PT. SXX using the Six Sigma approach through DMAIC stages (Define, Measure, Analyze, Improve, Control). The main issue identified is the high defect rate of 2.9%, or 1,971 defective units out of a total production of 67,705 sheets in 2024. The critical defect types include bubbles, delamination, and core holes. This quantitative research employs tools such as Pareto diagrams, fishbone diagrams, and 5 Whys analysis to trace the root causes of defects. The results indicate that the dominant factors are improperly dried raw materials, unstable machinery, uneven glue distribution, and a lack of supervision and SOP understanding among operators. Improvements were made through the provision of MC meters, glue spreader calibration, operator training, and improvement of veneer storage environments. Post-improvement, the defect rate is targeted to drop below 2.9%. This study also supports the implementation of Green Supply Chain Management (GSCM) by promoting energy efficiency and reducing production waste, thereby contributing to the improvement of product quality and competitiveness.